Pengaruh Keamanan Kerja dan Kompensasi terhadap Kinerja Karyawan Honorer dengan Komitmen Organisasi sebagai Mediasi - Alfian Noor; Rini Rahmawati; Ahmad Rifani (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
Improving the performance of non-permanent university staff poses a strategic challenge in human resource management, especially as insecure employment status often leads to uncertainty and decreased motivation. This study is motivated by a gap between the ideal expectation of optimal performance (das sollen) and the reality of job insecurity and inadequate compensation (des sein). The research aims to examine the influence of job security and compensation on the performance of honorary employees at Lambung Mangkurat University, with organizational commitment as a mediating variable. This research employed a quantitative approach using a descriptive-analytical survey design. A total of 128 respondents were selected through proportionate stratified random sampling from a population of 362 honorary staff across 12 work units. Data were collected using a structured questionnaire and analyzed with Structural Equation Modeling (SEM) using the Partial Least Squares (PLS) technique. The results reveal that both job security and compensation significantly influence performance, directly and indirectly through organizational commitment. Organizational commitment serves as a strong mediator, reinforcing the positive effects of the independent variables on employee performance. The study concludes that enhancing honorary staff performance requires comprehensive policies that strengthen job security, ensure fair compensation, and foster organizational commitment. It is recommended that the university provide clearer employment contracts, improve compensation systems, and create an inclusive and participative work environment to build long-term loyalty.